2012
DOI: 10.1002/art.34670
|View full text |Cite
|
Sign up to set email alerts
|

Difference in subchondral cancellous bone between postmenopausal women with hip osteoarthritis and osteoporotic fracture: Implication for fatigue microdamage, bone microarchitecture, and biomechanical properties

Abstract: Objective. Osteoarthritis (OA) and osteoporosis (OP) of the hip rarely occur in the same patient. The purpose of this study was to determine whether this difference might be attributable to the different quantity and quality of subchondral cancellous bone in the two conditions.Methods. Subchondral cancellous bone from the femoral head was obtained at the time of hip arthroplasty from 60 postmenopausal women, 30 with OA and 30 with OP. In each group, 10 specimens were subjected to compressive fatigue loading an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 50 publications
4
31
0
Order By: Relevance
“…Quantitative measurements revealed that the BV/TV, Tb.Th, Tb.N, and Conn.D values were decreased with BMD (Supplementary Table S1) ( P <0.05), which was consistent with a previous study. 24 The 3D μ CT figures and quantification charts (Figures 3a–i) also showed that microarchitectural changes coincided with BMD. Thus, the patient groups were cross-calibrated by BMD and μ CT; however, significant differences were not observed between the groups according to age ( P =0.065) (Supplementary Figure 3A and Supplementary Table S2).…”
Section: Resultsmentioning
confidence: 69%
“…Quantitative measurements revealed that the BV/TV, Tb.Th, Tb.N, and Conn.D values were decreased with BMD (Supplementary Table S1) ( P <0.05), which was consistent with a previous study. 24 The 3D μ CT figures and quantification charts (Figures 3a–i) also showed that microarchitectural changes coincided with BMD. Thus, the patient groups were cross-calibrated by BMD and μ CT; however, significant differences were not observed between the groups according to age ( P =0.065) (Supplementary Figure 3A and Supplementary Table S2).…”
Section: Resultsmentioning
confidence: 69%
“…This finding was expected based on previous morphometric guinea pig model of spontaneous OA 17,18 and human studies. [23][24][25][26][27][28][29] As an adaptation to OA, trabecular bone may increase its stiffness and strength [39][40][41] by changing its structure to resist higher loading due to cartilage loss.…”
Section: Discussionmentioning
confidence: 99%
“…In the 1970s, Radin and Rose 63 proposed that increased stiffness of subchondral bone might lead to articular cartilage degeneration through the mechanical effects of increased shear stress. However, subsequent studies using a variety of techniques at different stages of OA progression have revealed complex and opposing changes in apparent density, material density, and stiffness in osteoarthritic subchondral bone, [64][65][66] suggesting that this explanation is too simplistic. 40,67 Thinning of the articular cartilage from below, owing to reactivation of endochondral ossification at the bone-cartilage interface in OA joints resulting in tidemark duplication and advancement, may represent another important mechanism by which increased bone formation could drive the OA process.…”
Section: Mechanisms Including Recent Insights From Genetic Studiesmentioning
confidence: 99%